2014
DOI: 10.1186/1471-2458-14-971
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of a social support physical activity intervention in weight management among post-partum Latinas

Abstract: BackgroundWeight gain during the childbearing years and failure to lose pregnancy weight after birth contribute to the development of obesity in postpartum Latinas.MethodsMadres para la Salud [Mothers for Health] was a 12-month, randomized controlled trial exploring a social support intervention with moderate-intensity physical activity (PA) seeking to effect changes in body fat, fat tissue inflammation, and depression symptoms in sedentary postpartum Latinas. This report describes the efficacy of the Madres i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 79 publications
4
84
0
1
Order By: Relevance
“…The increase in family support was also maintained from post-treatment to follow-up. Sustaining gains in social support at follow-up has been a challenge for physical activity interventions as scores tend to return to baseline levels (Castro et al, 1999; C. Keller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in family support was also maintained from post-treatment to follow-up. Sustaining gains in social support at follow-up has been a challenge for physical activity interventions as scores tend to return to baseline levels (Castro et al, 1999; C. Keller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in family support was also maintained from post-treatment to follow-up. Sustaining gains in social support at follow-up has been a challenge for physical activity interventions as scores tend to return to baseline levels (Castro et al, 1999; C. Keller et al, 2014). The positive results in the present study may be attributed to targeting social support using different strategies including individualized assessments and feedback on support, tip sheets and newsletters providing practical ideas on garnering support, and a goal setting session that addressed support status at the post-treatment visit.…”
Section: Discussionmentioning
confidence: 99%
“…When asked about ways to improve engagement in the Facebook group, women in all three pilots suggested increased opportunities for in-person meetings or participation. However, previous research among low-income, postpartum women has consistently demonstrated poor engagement in weight loss intervention sessions [18,19,48], and when provided the opportunities to meet in person, women in Pilot 2 and Pilot 3 did not participate. Furthermore, engagement data across time did not differ across the studies, suggesting that our changes to the intervention posts did little to improve engagement from Pilot 1 to Pilot 2 to Pilot 3.…”
Section: Discussionmentioning
confidence: 99%